ANSWER
The equation is
![y - 5x + 20 = 0](https://tex.z-dn.net/?f=y%20-%205x%20%2B%2020%20%3D%200)
EXPLANATION
Let the equation be
![y = mx + c](https://tex.z-dn.net/?f=y%20%3D%20mx%20%2B%20c)
where
![m = 5](https://tex.z-dn.net/?f=m%20%3D%205)
is the slope of the line.
We substitute this value to obtain,
![y = 5x + c](https://tex.z-dn.net/?f=y%20%3D%205x%20%2B%20c)
Since the line passes through
![(4,0)](https://tex.z-dn.net/?f=%284%2C0%29)
we can use this point to determine the value of c.
We substitute this point to obtain,
![0 = 5(4) + c](https://tex.z-dn.net/?f=0%20%3D%205%284%29%20%2B%20c)
![0 = 20 + c](https://tex.z-dn.net/?f=0%20%3D%2020%20%2B%20c)
![c = - 20](https://tex.z-dn.net/?f=c%20%3D%20%20-%2020)
Our equation now becomes
![y = 5x - 20](https://tex.z-dn.net/?f=y%20%3D%205x%20-%2020)
We can write this in standard form as
Answer:
d. y=5x-3
Slope-intercept form is y=mx+b.
m= slope
b= y intercept
so, m=5 and b= -3
Substitute with those values and then you have the equation.
Answer:
11/20
Step-by-step explanation:
Finding the common denominator, which is 20, we convert 1/5 into 4/20 and 1/4 into 5/20. Adding those up, the remainder when subtracted from 1, the total, is 11/20.
1) -3
2) 6
3) 4
4) 2
5) 5
6) 5
7) 7
8) -3
9) 9
10) 6
11) -5
12) 0
Here are your answers may I please have the brainliest
Answer:
(0, -1)
Step-by-step explanation:
There are multiple ways of solving this however- since both equations are already in Y-Intercept form, we will use the "Equal Values Method"
First, since both equations are equal to Y, we can set them equal to each other and solve for X
![\frac{3 }{4} x - 1 = \frac{4}{3} x - 1](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%20%7D%7B4%7D%20x%20-%201%20%3D%20%20%5Cfrac%7B4%7D%7B3%7D%20x%20-%201)
To start, you must eliminate the fraction using a "fraction buster" multiply EVERYTHING by 4 then simplify.
![3x - 4 = 5 \frac{1}{3}x - 4](https://tex.z-dn.net/?f=3x%20-%204%20%3D%205%20%5Cfrac%7B1%7D%7B3%7Dx%20%20-%204)
Since we still have a fraction, we shall do it one more time. This time we multiply by 3
![9x - 12 = 6 x - 12](https://tex.z-dn.net/?f=9x%20-%2012%20%3D%206%20x%20-%2012)
Now, solve how you normally would.
9x = 6x
-6x
3x = 0
X = 0
Now, since we know what X would equal in the solution, we are able to plug in X as 0 in one of our equations. We can choose the first one!
![y = \frac{3}{4} (0) - 1](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B3%7D%7B4%7D%20%280%29%20-%201)
Now solve which would lead to y = -1
You have your solution as
(X,Y)
(0,-1)
Hope this helps!